Rancang Bangun Freewheeling DC Terkontrol Untuk Menunjang Praktikum Elektronika Daya - I Wayan Lastera (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2022)
Controlled DC is a type of DC voltage ignition involving power electronic components, as an effort to meet the electrical power needs of certain loads, whether resistive, inductive or capacitive. In power electronics practicum, controlled DC testing with inductive loads is less than optimal due to equipment limitations. To overcome this, in this research a controlled DC freewheeling design was created and tests were carried out: 1. Controlled DC testing with a resistive load in series with an inductive whose inductance value was varied without applying freewheeling. 2. Controlled DC testing with a resistive load in series with an inductive load whose inductance value is varied by applying freewheeling. The aim of this research is to determine the potential of freewheeling design, as an effort to further optimize controlled DC performance testing with resistive, inductive and capacitive loads in power electronics practicum. The test data obtained was tabulated, analyzed descriptively. The results obtained show that in test 1, the DC output voltage has a part left on the negative side. In test 2, the DC output voltage has no part left on the negative side. Freewhweeling functions well and makes testing in power electronics practicum more optimal.